(untitled) (Journal of Medical & Health Sciences Review, 2025)
Anemia is characterized by low iron levels in the human body is a prevalent global health issue, particularly in less developed countries. The objectives of the study were to Investigate the prevalence of anemia (IDA) among different age groups in district Mardan and examine management strategies employed by Participants. A well-defined questionnaire was used to collect the information from 100 participants. The questionnaire consists of Sociodemographic information, bleeding disorder, family history, symptoms of anemia, and management strategies used. Rapid Iron Spot Test Kits from Nuclear Institute for Food and Agriculture (NIFA) were used to test the iron content in wheat flour. Information about dietary consumption was assessed with the help of the Food Frequency Questionnaire. Results showed that anemia was most prevalent in unmarried females with fatigue being the most common symptom. The major cause of anemia was less incorporation of iron-rich foods in their diet. Consumption of iron-rich foods, Vitamin-C-rich foods, iron supplements, and education & awareness on iron deficiency anemia and its management would be effective in reducing anemia.